Strategy for Sustainable Bio‐Value Chain Development: Algal Biomass Utilization Without Inhibitory Effects on Lactic Acid Production via Efficient Diluted Acid Hydrolysis of Brown Macroalga - Jihyun Bae; Jeongho Lee; Hyeok Ki Kwon; Giwon Lee; Taek Lee; Hyun Gyu Lim; Sang Woo Seo; Gyoo Yeol Jung; Hah Young Yoo; Chulhwan Park (GCB Bioenergy)
ABSTRACT Saccharina japonica, one of the most widely cultivated brown algae species, is considered a promising biorefinery feedstock due to its high carbohydrate content. Dilute acid hydrolysis can be performed to recover sugars from S. japonica; however, the impact of sugar derivatives (potential inhibitors) generated during the hydrolysis process on lactic acid production remains unexplored. In this study, the inhibitory effects of sugar derivatives on the fermentation performance of Lacticaseibacillus rhamnosus were systematically examined to enhance the bioconversion efficiency of S. japonica. Firstly, the sugar derivatives present in S. japonica hydrolysate were identified, revealing the presence of acetic acid, formic acid, and furfural. Subsequently, their inhibitory effects on lactic acid production were assessed, demonstrating significant inhibition (p < 0.05) at the following concentrations: > 2 g/L acetic acid, > 0.5 g/L formic acid, and > 1 g/L furfural. Based on the information, 5% H2SO4 was determined to be the optimal solvent for S. japonica hydrolysis, enabling the production of hydrolysate with high fermentable sugar content and minimal sugar derivatives: 23.23 g/L mannitol, 0.86 g/L glucose, 0.21 g/L acetic acid, 0.14 g/L formic acid, and no detectable furfural. The resulting S. japonica hydrolysate contained sugar derivatives at non‐inhibitory levels, allowing for direct application to fermentation without detoxification. As a result, lactic acid production and yield were determined to be 18.26 g/L and 92.3%, respectively, comparable to the control group (17.32 g/L and 87.6%). This study addresses a critical knowledge gap in the bioconversion of macroalgae to lactic acid by elucidating the effects of sugar derivatives on fermentation performance.